2003
DOI: 10.1038/sj.bjp.0705488
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine‐induced IL‐6 expression in pituitary folliculostellate cells is mediated via A2b adenosine receptors coupled to PKC and p38 MAPK

Abstract: 1 Activation of adenosine receptors in folliculostellate (FS) cells of the pituitary gland leads to the secretion of IL-6 and vascular endothelial growth factor (VEGF). 2 We investigated the action of adenosine A2 receptor agonists on IL-6 and VEGF secretion in two murine FS cell lines (TtT/GF and Tpit/F1), and demonstrated a rank order of potency, 5 0 -Nethylcarboxamidoadenosine (NECA)42-p-(2-carboxyethyl)phenethylamino-5 0 -N-ethylcarboxamidoadenosine4adenosine, suggesting mediation via the A2b receptor. 3 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 41 publications
(49 reference statements)
7
42
0
Order By: Relevance
“…Genes that have a transcription role include thioredoxin-interacting protein (Txnip), kruppellike factor 6 (Klf6) core-binding factor, runt domain, alpha subunit 2; translocated to, 2 (CBFA2T2) and NK2 transcription factor related, locus 2 (NKX2-2). A repression of growth-inhibitory genes is consistent with our previous data where we showed that adenosine acting through A2 receptors stimulated the proliferation of TtT/GF cells [16].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Genes that have a transcription role include thioredoxin-interacting protein (Txnip), kruppellike factor 6 (Klf6) core-binding factor, runt domain, alpha subunit 2; translocated to, 2 (CBFA2T2) and NK2 transcription factor related, locus 2 (NKX2-2). A repression of growth-inhibitory genes is consistent with our previous data where we showed that adenosine acting through A2 receptors stimulated the proliferation of TtT/GF cells [16].…”
Section: Discussionsupporting
confidence: 93%
“…Those genes that are upregulated contain several members that are associated with cytokine synthesis and immune function and membrane receptor activity and those that were inactivated were associated with anti-proliferation and transcription. IL-6 mRNA expression increased at both time points, (0.5 (30-fold) and 2 h (100-fold), consistent with our previous data on secretion [16]. Three transcription factors, NR4A1, NR4A2 and BHLHB2 (basic helix loop-helix domain containing class B2; cluster 5) were also transiently switched on at the 30-min time point before falling back to basal levels at 2 h. Of particular interest was increased expression of two related genes THBD and EPCR which are usually associated with endothelial cells and blood coagulation but have also been linked with anti-inflammation and anti-apoptosis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations